Nutrient-Mediated Activation of Cellular Signaling Pathways: Mechanistic Insights into Attenuation of Toxin Induced Inflammation in Food Animals - Md. Emran Hossain (International Journal of Toxins and Toxics, 2026)
Dietary and environmental toxins remain a persistent challenge in food animal production, where subclinical and clinical inflammation compromises health, productivity, and food safety. Toxin induced inflammation is driven by oxidative stress, mitochondrial dysfunction, and dysregulated immune signaling, resulting in impaired metabolic efficiency and increased disease susceptibility. Recent advances in nutritional science have revealed that nutrients act not only as substrates for growth but also as signaling molecules capable of modulating key cellular pathways involved in inflammatory regulation. This review synthesizes current knowledge on nutrient mediated activation of cellular signaling pathways and their mechanistic roles in attenuating toxin induced inflammation in food animals. Major nutrient sensing and stress responsive pathways, including AMP activated protein kinase, mechanistic target of rapamycin, nuclear factor erythroid two related factor two, nuclear factor kappa B, and mitogen activated protein kinases, are discussed in the context of toxin exposure. The review highlights how specific nutrients such as amino acids, fatty acids, vitamins, minerals, and functional phytogenic compounds influence these pathways to restore redox balance, regulate cytokine production, enhance cellular detoxification, and maintain mitochondrial integrity. Species specific responses in poultry, ruminants, and swine are also considered, reflecting differences in digestive physiology and metabolic regulation. In addition, emerging tools including nutrigenomics, metabolomics, and systems biology approaches are evaluated for their potential to clarify complex nutrient toxin signaling interactions. By integrating mechanistic insights with applied nutritional strategies, this review provides a framework for 2 | Page developing precision feeding interventions aimed at reducing inflammation, improving resilience to toxins, and enhancing sustainable food animal production. The findings underscore the importance of signaling based nutrition as a promising avenue for mitigating toxin related challenges in modern livestock systems.
Keywords: AMPK; Nrf2; Oxidative stress; inflammation; mTOR; nutrient signaling; toxin exposure